Pengembangan Industri Kreatif Sirup Belimbing Wuluh untuk Pemberdayaan UPPKS Terampil Mandiri - Sundoro, Totok; Krisyanto; Nurjalil, Ade (DHARMA BAKTI, 2022)
During the current Covid-19 pandemic, which makes the community's economy difficult, the home industry is a brilliant solution, especially for people with disabilities. There is no stipulation on how much minimum capital to start, let alone age limit. Enough with a modest injection of funds, will, and persistence. The home industry can help people with disabilities in meeting the costs of their daily needs. The assumption that work must be a worker in a company or institution needs to be felt is not true. Building a home industry can also provide a large income, without having to work in someone else's place. Not only profit for ourselves, the home industry can also provide benefits to the people around us. If the home industry has grown large, it can absorb labor so as to improve the welfare of the community. With the good development of home industries in an area, it is hoped that in the future there will be many home industry units that produce similar products, such as the Independent Skilled UPPKS chaired by Mrs. Titi Sayekti, SKM which has the ability to process starfruit into syrup and can be developed into industry. Household Products Starfruit Syrup with high economic value. It is hoped that this can be followed by other household units in the vicinity, by making efforts to make their products more attractive to consumers. This is where the creativity of producers plays an important role. So in addition to the media collecting rupiah, the home industry indirectly stimulates creativity in the perpetrators. In the creative industry development activities that are carried out, they produce works in the form of "Kardiman Starfruit Syrup".